2023
DOI: 10.3390/ijms242316917
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Endophytes in Improving Salt–Alkali Tolerance and Salinity Resistance in Plants

Xueying Guo,
Wanrong Peng,
Xinyi Xu
et al.

Abstract: Ensuring food security for the global population is a ceaseless and critical issue. However, high-salinity and high-alkalinity levels can harm agricultural yields throughout large areas, even in largely agricultural countries, such as China. Various physical and chemical treatments have been employed in different locations to mitigate high salinity and alkalinity but their effects have been minimal. Numerous researchers have recently focused on developing effective and environmentally friendly biological treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…This study provides a description of the bacterial communities in soils with different levels of salinity and sodicity, which could provide a starting point for restoring these fragile habitats 72 . Most likely, the most significant agricultural application is the isolation of haloalkalitolerant bacteria from saline-alkaline environments with plant growth-promoting properties to support crop plant health and resistance against soil salinity [73][74][75] .…”
Section: Discussionmentioning
confidence: 99%
“…This study provides a description of the bacterial communities in soils with different levels of salinity and sodicity, which could provide a starting point for restoring these fragile habitats 72 . Most likely, the most significant agricultural application is the isolation of haloalkalitolerant bacteria from saline-alkaline environments with plant growth-promoting properties to support crop plant health and resistance against soil salinity [73][74][75] .…”
Section: Discussionmentioning
confidence: 99%
“…According to Khalvandi et al (2021) [42] reported as M. piperita plants were grown with S. indica and exposed to 9 dS/m of salt stress, their Na+ level dropped by 54.37% compared to plants that were not infected. While the exact methods via which endophytes enhance salt tolerance in their host plants remain unclear, it is hypothesized that this process may involve the production of stress-responsive hormones in the host, the activation of stress-responsive genes in the host [43], and the active maintenance of a low ratio of sodium (Na + ) to potassium (K + ) [44,45]. Our study revealed that endophytic fungi demonstrated the highest resilience to salt stress when grown on PDA plates with varied concentrations of NaCl, as evidenced by their maximal colony growth rate.…”
Section: Discussionmentioning
confidence: 99%